PORE SOLUTIONS IN THE ROCKS OF THE SCHLEMA URANIUM DEPOSIT, ERZGEBIRGE, AND THEIR ROLE IN ORE FORMATION - Barsukov Vikt.L. (My University, 2004)
More than 93% of the uranium in the Schlema deposit (Erzgebirge) occurs in veins within a compositionally diverse rock unit, which are referred to as the productive series. Physicochemical reasons for the confinement of uranium vein ores to this unit are still debated. Computer modeling demonstrated its high reducing capacity. Under any reasonable conditions (Cl/CO2, temperature, pressure, and water-rock ratio), the pore solutions of all productive series, both silicic and basic, show Eh values 350-400 m V lower than the pore solutions of barren leucocratic rocks occurring outside and, in part, inside this member. The compositions and properties of pore solutions from all productive rocks allow them to play the role of a mobile selective uranium reducer, whose influence can promote vein-type uranium ore deposition from ore-bearing hydrothermal solutions.